2013
DOI: 10.3892/or.2013.2726
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of baicalin and wogonoside with glycoside hydrolase: A promising approach to enhance anticancer potential

Abstract: Previous phytochemical studies showed that the major flavonoids in Scutellaria baicalensis are baicalin, baicalein, wogonoside and wogonin. The two glycosides (baicalin and wogonoside) can be transformed into their aglycons (baicalein and wogonin), which possess positive anticancer potential. In this study, we used glycosidase to catalyze flavonoids in S. baicalensis to enhance the herb’s anticancer activities. Our HPLC data showed that, using the optimized conditions obtained in our experiments (20 U/g of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…This is further supported by a recent publication showing that pretreatment of baicalin with glycoside hydrolase substantially enhanced its antiproliferative activity in human colorectal and breast cancer cells [19].…”
Section: Discussionsupporting
confidence: 57%
“…This is further supported by a recent publication showing that pretreatment of baicalin with glycoside hydrolase substantially enhanced its antiproliferative activity in human colorectal and breast cancer cells [19].…”
Section: Discussionsupporting
confidence: 57%
“…In this work, we distinguished the quenching types on the basis of the calculation calculated KSV received at different temperature. 8 For a fluorescence quenching process, the decrease in intensity is usually described by the well-known Stern-Volmer equation: 31 [ ]…”
Section: Quenching Mechanismmentioning
confidence: 99%
“…6,7 Baicalein ( Figure 1A) and wogonin ( Figure 1C) are flavones originally isolated from Scutellaria baicalensis, a chinese medicinal plant with various biological properties. 8,9 These polyphenolic benzo-γ-pyrone compounds have attracted great interest since the 1990s due to growing evidence of their pharmacological effects, including antiallergenic, antiviral, antiinflammatory, antitumor and vasodilating activity. [10][11][12][13] Deoxyribonucleic acid (DNA) has long stood as a unique polymer due to its role in biology and biochemistry, 14 contains the genetic instructions for the development and functioning of living organismsis, the target molecule for many drugs, especially antitumor therapies, 15,16 always to be the hot topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…It effectively inhibits the activity of hepatocellular carcinoma cells, colorectal cancer cells, cervical cancer cells, breast cancer cells and other tumor cells (17). In recent years, the study of the molecular mechanism of traditional Chinese medicine and its effective constituents in inhibiting tumors have made a lot of progress, resulting in various findings, including the inhibition of tumor growth by inducing cell apoptosis, cell toxicity, regulating cell signal transduction, inducing cell differentiation, reversing multidrug resistance and suppressing the activity of telomerase (16)(17)(18). In the present study, the potential anticancer effect of wogonoside on human colon cancer cells was demonstrated.…”
Section: Introductionmentioning
confidence: 99%